Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1515/jpme.1996.24.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytokine levels of amniotic fluid and histological chorioamnionitis in preterm delivery

Abstract: The aim of this study was to investigate the correlation between the cytokine levels in the amniotic fluid (AF) and the histological stage of chorioamnionitis (CAM) in premature labor. AF of 6 cases (7 samples of AF were obtained as one was a twin pregnancy) in whom CAM was diagnosed histologically, and 12 cases without CAM were included in this study. Amniotic fluid was obtained within 24 hours prior to delivery. Cytokine levels (IL-2, -4, -6, TNF-alpha, IFN-gamma) in AF were measured by an ELISA method. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…The localisation of both irIL-4 and IL-4R reported by De Moraes-Pinto et al [8] is consistent with that observed in the present study. Immunoreactive IL-4 has been also detected in amniotic fluid obtained from women at term [20,21]. Furthermore, the concentration of irIL-4 in amniotic fluid was not affected by labour status at term [21].…”
Section: Discussionmentioning
confidence: 88%
“…The localisation of both irIL-4 and IL-4R reported by De Moraes-Pinto et al [8] is consistent with that observed in the present study. Immunoreactive IL-4 has been also detected in amniotic fluid obtained from women at term [20,21]. Furthermore, the concentration of irIL-4 in amniotic fluid was not affected by labour status at term [21].…”
Section: Discussionmentioning
confidence: 88%
“…The authors found that regardless of the gestational age at rupture, IL-6 from amniotic fluid was the best predictor of HCA. Several other authors have established the importance of inflammatory markers such as IL-8, IL-10, and TNF-α for the prediction of HCA in PPROM [25][26][27][28]. Nonetheless, very few studies had established the role of maternal serum inflammatory markers for the prediction of PPROM.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 appears not to be produced during normal pregnancies but only in certain pathological conditions, including infectious processes. Negishi et al (25) published findings correlating elevated levels of IL-2 within amniotic fluid with evidence of histologic chorioamnionitis (25). IL-2 secretion has also been implicated in the pathogenesis seen in deranged vasculature of the placenta associated with preeclampsia (11).…”
Section: Discussionmentioning
confidence: 99%